The Role of Sport in Achieving Sustainable of Athletic Women in Northern Governorates of Palestine - Hethnawi, Maryam; Amara, Sofiene; Boukari, Samia; Abdelhaq, Imad; Ben Amar, Imen; Chortane, Sabri Gaied; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2023)
The study aimed to identify the role of sports in achieving the sustainable development of women in the Palestinian society, and to identify the level of knowledge of the study sample of the concept of sustainable development. Two areas, and the study population included all workers in some Palestinian institutions in the northern governorates of Palestine. The study sample consisted of (2040) respondents. The sample studied for the role of sport in achieving sustainable development for women also came to a moderate degree, with an arithmetic mean (3.22). The study recommended the need to promote the concept of sustainable development within the Palestinian educational curricula and sports circles, and to strengthen the sports strategies of Palestinian institutions for the important role of sport in achieving sustainable development.